Primary caesarean section in multigravida - Munusamy, Mohana Dhanapal; Sengodan, Subha Sivagami; Duraisamy, Kalaivarasi Umapathy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: This study was done to analyse primary caesarean section in multigravida who had delivered vaginally. Indications for caesarean section were studied in relation to age, gravida, maternal and foetal morbidity. Methods: This study was conducted in Goverment Mohankumaramangalam Medical College and Hospital, Salem. It was a retrospective study from September 2016 to August 2017. Results: Most of cases were referred as an emergency. Most common age group was between 20-30 years. Majority were second gravida. Among the various indications for primary caesarean section in multigravida, foetal distress (18.12%), hypertensive disorder complicating pregnancy (16.10%), CPD (15.43%), APH (12.08%), malpresentation (10.73%) were the common indications. In intraoperative complication PPH was most common (16.77%). In postoperative complication fever was the most common (20.80%). Still birth occurred in 10.06% of cases, 42 babies were admitted in NICU and babies had APGAR >7 (61.74%). Conclusions: Implementation of standard labour management strategies can decrease primary caesarean rate without compromising maternal and foetal safety. We must encourage early referral of high risk patient, so that the patient can reach higher centre earlier and proper management could be done before consequences become grave.